2005
DOI: 10.1159/000084024
|View full text |Cite
|
Sign up to set email alerts
|

Communication between the Perilymphatic Scalae and Spiral Ligament Visualized by in vivo MRI

Abstract: We evaluated the transport of Gadolinium-diethylenetriaminepentaacetate-bismethylamide (Gd-DTPA-BMA) through the round window (RW) membrane into the perilymphatic space with 4.7-T MRI in an animal study and 1.5-T MRI in humans. After administration of Gd-DTPA-BMA onto the intact RW membrane of guinea pig, Gd-DTPA-BMA uptake was observed in the basal turn and part of the second turn within 40 min. The scala tympani, scala vestibuli, the fibrous part of the spiral ligament and semicircular canal all showed uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 41 publications
(24 reference statements)
6
83
0
5
Order By: Relevance
“…Prior studies have reported higher levels in scala vestibuli than scala tympani (Zou et al 2005. Several possibilities have been postulated to explain this including a connection to calcium channels (Zou et al 2005) and the potential additional passage through the annular ligament around the stapes footplate (Zou et al 2005; however, no one has yet interpreted their findings quantitatively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies have reported higher levels in scala vestibuli than scala tympani (Zou et al 2005. Several possibilities have been postulated to explain this including a connection to calcium channels (Zou et al 2005) and the potential additional passage through the annular ligament around the stapes footplate (Zou et al 2005; however, no one has yet interpreted their findings quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…When performed at different times after application, this allows a more complete picture of drug distribution in the ear as a function of distance and time to be established. In previous studies, the technique has generally been used to document the Gd distribution qualitatively (Zou et al , 2005Counter et al 2003), but in this study, we have analyzed the data semiquantitatively. The analysis leads us to the novel conclusion that in most ears, the observed distribution of Gd-DTPA cannot be accounted for solely by entry from the RW niche into ST through the RW membrane, with subsequent local redistribution from ST to SV in the basal turn.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations